The Effect of Uric Acid as a Predisposing Factor on Polyneuropathy in Patients with Type 2 Diabetes Mellitus - Rafie, Shahram; Alemi, Fatemeh; Shamsaei, Gholam Reza; Zakerkish, Mehrnoosh; Yazdanpanah, Leila (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Background: Since serum uric acid is a controllable and modifiable factor in diabetic patients, identifying the risk factors and accelerating the incidence of neuropathy in these patients plays an important role, and can reduce its level, and the patient's disability, as well as additional therapeutic costs for the patient and the health system in the country. Method: In this retrospective cohort study conducted at the Golestan Hospital in 2015-2017, the study population was 100 type 2 diabetic patients based on NCS of 54 patients with polyneuropathy. First, the demographic data on clinical examinations, lab tests, and uric acid levels in these patients were recorded on a checklist. Then, in 2017, patients were reassessed for clinical investigations and lab tests, and all data entered on the previous checklist. Finally, all the data were analyzed using the SPSS v23. Results: The mean age of patients with polyneuropathy was 51.77 years, and there was a significant relationship between age, BMI and duration of diabetes with neuropathy, but there was no significant difference in gender, smoking and hypertension. The mean serum level of uric acid in the two years ago was 3.85 mg/dl, and at the time of the study, it was 4.18±1.55 mg/dl. There was no significant difference in serum levels of this substance after two years of follow up in patients with polyneuropathy (P=0.139). The incidence of polyneuropathy was reported by NCS findings of 54%. In other words, 54% of diabetic patients developed diabetic polyneuropathy for two years. Conclusion: Polyneuropathy is a common complication in diabetic patients, and the serum levels of uric acid over time cannot have a significant effect on the incidence of this disorder.